KONSEP DASAR SEMIGRUP REGULER REDUKTIF - Persulessy, Elvinus R. (PATTIMURA UNIVERSITY, 2007)
In this paper, we consider the properties of reductive semigroups, with two congruence relations defined on them, which gave a characterization for regular reductive semigroups.